2016
DOI: 10.1128/jvi.00852-16
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor T Cells Guided by the Single-Chain Fv of a Broadly Neutralizing Antibody Specifically and Effectively Eradicate Virus Reactivated from Latency in CD4 + T Lymphocytes Isolated from HIV-1-Infected Individuals Receiving Suppressive Combined Antiretroviral Therapy

Abstract: Despite the advent of combined antiretroviral therapy (cART), the persistence of viral reservoirs remains a major barrier to curing human immunodeficiency virus type 1 (HIV-1) infection. Recently, the shock and kill strategy, by which such reservoirs are eradicated following reactivation of latent HIV-1 by latency-reversing agents (LRAs), has been extensively practiced. It is important to reestablish virus-specific and reliable immune surveillance to eradicate the reactivated virus-harboring cells. In this rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 69 publications
1
100
0
Order By: Relevance
“…Finally, current programs and protocols for HIV eradication, including histone deacetylase inhibitor (HDACi) administration and immunotherapy, reportedly need improved immunotherapeutic strategies to clear virus in reactivated cells and to limit new virus integration (43,55,59,72,73). Selection and expansion of NK cells with high NCR and IFN-␥ inducibility may represent a useful tool to efficiently clear HIV-1 when combined within the frame of virus eradication strategies exploiting latency exit induction and immuno-/antiretroviral therapy (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, current programs and protocols for HIV eradication, including histone deacetylase inhibitor (HDACi) administration and immunotherapy, reportedly need improved immunotherapeutic strategies to clear virus in reactivated cells and to limit new virus integration (43,55,59,72,73). Selection and expansion of NK cells with high NCR and IFN-␥ inducibility may represent a useful tool to efficiently clear HIV-1 when combined within the frame of virus eradication strategies exploiting latency exit induction and immuno-/antiretroviral therapy (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…Selection and expansion of NK cells with high NCR and IFN-␥ inducibility may represent a useful tool to efficiently clear HIV-1 when combined within the frame of virus eradication strategies exploiting latency exit induction and immuno-/antiretroviral therapy (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…[71][72][73][74][75][76][77][78][79][80] used measure of the viable HIV reservoir) and rectal HIV DNA (-0.5 log), and a trend toward less viral rebound, although no decrease in peripheral blood HIV DNA or rectal HIV RNA. 81 Long-term follow-up suggests that this approach was safe and results in long-lived cells with CAR DNA that persisted for more than a decade.…”
Section: Previous Trials Of Anti-hiv Carmentioning
confidence: 99%
“…Upon assessment in a suite of assays, each of these CARs is functional; however, efficiency varies with each ligand-binding moiety, each assay used, and the virus strain being employed. Importantly, Liu et al 42 recently reported that…”
Section: Kitchen and Zackmentioning
confidence: 99%
“…32,42 Some of these CARs also contain additional signaling sequences, which provide costimulatory capability upon ligand binding, to achieve a more robust activation event upon ligation with the target epitope. Upon assessment in a suite of assays, each of these CARs is functional; however, efficiency varies with each ligand-binding moiety, each assay used, and the virus strain being employed.…”
Section: Kitchen and Zackmentioning
confidence: 99%